Price and Income Dynamics in the Agri-Food System: A Disaggregate Perspective - Joseph Baines (The Bichler and Nitzan Archives, 2015)
This dissertation seeks to illuminate contemporary processes of redistribution in the agri-food sector, with particular reference to the US. It addresses the following questions: How has the rapid rise in food price instability since the turn of the twenty-first century impacted income shifts within the agri-food system? Which groups within agriculture and agribusiness benefit from high and volatile food prices and which groups have suffered amid the tumult? Are all of these groups 'price-takers' that simply respond to price signals? Or are some of them 'priceshapers' that, with varying degrees of success, actively seek to restructure the agri-food system, and the regulatory architecture that governs it, in ways that make certain price developments more likely? Hitherto, there has been little in the way of sustained analysis of the connections between prices, power and redistribution in the agri-food system. The dissertation addresses three approaches that offer some perspective on the redistributional-power dynamics of agricultural commodity price movements: global value chains analysis, the food regime approach and the emergent international political economy literature on post-crisis commodity derivatives regulations. As the thesis argues, although these approaches offer important qualitative insights, they have yet to offer quantitative means of gauging the power-shifts between different agricultural and agribusiness groups and their connection to price-shifts between different agri-food sub-sectors. The thesis attempts to enfold the multiple insights of the existing literature into the capital as power approach. I submit that the process of enfoldment results in an analysis that offers a rich and highly differentiated understanding of the redistributional dynamics of high and volatile agricultural commodity prices. The arguments are made in relation to the contestation within agriculture and agribusiness over perhaps the two most controversial developments within the US agri-food sector in the early twenty-first century: the diversion of grain into agrofuels production and the rise of 'excessive speculation' in agricultural derivatives markets. The importance of these two developments is underlined by the fact that a number of scholars have attributed the sharp food price peaks in 2007-08 and 2010-11 to the influx of speculative investment in futures markets, and the general upward trend in food prices in the 2000s to the agrofuel boom. By analyzing the redistributional effects of high and volatile prices, and by examining the contestation over the course taken by agrofuels policy and commodity derivatives regulation, the dissertation outlines the winners and losers of high and volatile food prices within both agribusiness and agriculture. [This thesis was nominated for the York University Dissertation Prize.]
Additional information: Unpublished PhD Dissertation, Political Science, York University, 2015
Keywords: 330; biofuels; capital accumulation; capital as power; ethanol; dietary shifts; food regimes; global value chains; livestock; production; redistribution; renewable energy